The principle of democratic teleology in international law - Niels Petersen (Max Planck Institute for Research on Collective Goods, 2008)
In the early 1990s, after the fall of the Berlin wall, legal scholars initiated a debate on the existence of a right to democratic governance in international law. Many of the adherents to the democratic entitlement school seem to assume that democratization is a simple shift in the political status, a change from one form of government to another. This contribution seeks to analyze this underlying assumption by taking a look at the current discussion on democratization theory in the political sciences. Through this lens, it will reconsider the international practice and the corresponding legal documents related to the existence of a possible democracy principle. In this respect, a special emphasis will be put on three areas of potential precedents resolutions of the UN General Assembly, the practice of regional organizations such as the Organization of American States or the African Union, and military interventions in the name of democracy. The analysis will show that the legitimacy principle of international law is, at the same time, more modest and more demanding than the claim of the democratic entitlement school. It will be argued that democracy is no strict obligation, but rather a teleological principle. States are obliged to develop towards democracy and to consolidate and to optimize democracy, once electoral institutions have been established.
Keywords: 340; Demokratisierung; Völkerrecht; Welt